Modern Information Technologies and Services in Public Institutions - Piatnychuk, Iryna; Pyatnychuk , Halyna (Journal of Vasyl Stefanyk Precarpathian National University, 2021)
The article considers the issues of modern information technologies and services in public institutions (on the example of educational institutions). The aim of the article is to study the application of modern information technologies and services, in particular Google services, in such public institutions as educational institutions during the pandemic and to identify opportunities for their wider use. Based on a study to assess the economic benefits of using Google services, it has been found that their wider use in educational institutions will also have a positive effect. It is determined that the use of the service "Google" allows you to solve problems of information support of management and educational processes in the educational institution, work together on different types of documents, avoid distortion of information while working on them by different users by setting the appropriate level of document access. Based on the study, it is proposed to classify Google services for the purposes of scientific and pedagogical work of teachers of educational institutions on the following grounds: general services; services for self-organization and productivity; services for educational purposes; services for scientific purposes; services for commercial and other purposes. It is established that in order to increase the efficiency of different goals, it is advisable to combine Google services for different purposes, such as general, educational and to increase productivity. It has also been established that the collaboration with Google services is organized at the excellent level necessary to work with documents and quickly access the information, taking into account the current conditions of the pandemic. The analysis of the directions of education reform and the possibilities of application of information technologies during their implementation gives grounds to assert that the decisive factor in achieving the main goals of education reform is its informatization. And the use of modern information technologies and services helps to increase the self-organization and productivity of the administration of the educational institution, teachers and students, to optimize educational and management processes. The results of the study are the basis for further research in terms of more effective use of modern information technology and services in public institutions on the example of educational institutions.